Adolescent triple-negative breast cancer with germline pathogenic variants in both BRCA1 and TP53 genes: A case report - Chen, Dongmei; Zhang, Chenyang; Yuan, Mengqi; Zhang, Ying; Liu, Qing; Wan, Donggui (Frontiers in Oncology, 2022)
Almost 5-10% of breast cancer results from inherited gene pathogenic variants (PVs). Patients with PVs in high-penetrance genes such as TP53, BRCA1 and BRCA2 are susceptible to breast cancer. Moreover, nearly 80% of BRCA PVs carriers are diagnosed with breast cancer at a young age before menopause. There is currently no report of early onset breast cancer with germline PVs in both BRCA1 and TP53 genes. Here, we report the case of a 14-years-old female diagnosed with triple-negative breast cancer (TNBC) with a family history of malignant tumors. The cancer metastasized to multiple lymph nodes 1 year and 4 months after surgery, and the progression-free survival (PFS) after subsequent chemotherapy and surgery has been 2 years and 10 months. The patient’s white blood cells were screened against a panel of 11 cancer-related genes, and both germline PVs in BRCA1 and TP53 were identified. Genetic tests on the patient’s family members revealed the same PV in BRCA1 in her father and brother, but BRCA1 PV wasn’t shown in other family members. The case indicates that genetic testing needs be performed in early onset breast cancer to confirm inherited risk, and if a germline PV is identified, tailored therapeutic interventions and preventive interventions should be taken and genetic testing is recommended for relatives.